การลดความสูญเปล่าของสายการผลิตกุ้งแปรรูปซูชิแช่แข็ง - ภัทร์วุธ บุญลาภ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The purpose of this research is guiding study about waste reduction in production process of sushi frozen shrimps. This research applied Lean Six Sigma concept wich emphasize waste reduction in production process combined with Six Sigma concept which as a method in this research. It consists 5 phase, which are define phase, measurement phase, analysis phase, improvement phase, and control phase. In each phase of waste reduction in production process of sushi frozen shrimps research divine up the work in 5 phase. The first phase is define 7 wastes for study all production line of sushi frozen shrimps. In each production process was founded 27 waste factors. Measurement phase was used screening mathode by cause and effect matrix which reduce the 27 waste factors to 9 waste factors and analysis factor by FMEA can be screening factor for improve process remain 5 factors. Improvement phase was describe the process improvement by participate with factory case study allocate and responsibility to implicated team. After the production process improvement, The result effect are reduce Takt time 32.46%, reduce the direct labor from 264 persons to 205 persons and reduce defect 61.45%. This research was improve only in 5 waste factors which utmost effect to the waste. Furthermore, We can reduce waste from the rest of cause then the waste trends to decline.